Is Nepal on the Verge of Economic Crisis? A Comparative Study of Sri Lanka and Nepal - Pandey, Mahesh (Journal of Advanced Academic Research, 2022)
This paper attempts to analyze the economic condition of Sri Lanka and compare it with that of Nepal especially based on external sector indicators. The main objective of this study is to identify the level of risk that economic crisis looming in Nepal by examining and comparing indicators using secondary data collected from various publications of the government of Nepal and Sri Lanka, central banks of both countries, World Bank, IMF and others across six years starting from 2016 to 2021. This Study follows the comparative and descriptive research design and analysis has gone through the same. The data and calculated indicators suggest that Sri Lankan economy had gone through bad phases after year 2019 and that led to acute crisis. The external sector indicators of Nepal show that Nepal was also facing some sort of issues after COVID-19 pandemic followed by Russia-Ukraine war in 2020 and 2021 however, there are encouraging signs of recovery in recent times. The study came with the conclusion that the economic crisis caused by drained of foreign exchange reserve has given a wakeup call to small growing economies and Nepal is not an exception. However, as a result of the precautionary policies and measures that Nepal has taken so far, the external sector’s indicators not showing worrying syndrome for severe economic crisis. To avoid the crisis in medium and long term Nepal should take initiatives for policy and structural reforms to enhance its productive capacity to induce export, tourism and other industries.